Associations between monthly fine particulate matter and ozone exposure, and postneonatal infant mortality in the United States, 2005–2017 - Sanjida J. Mowla; Alison K. Krajewski; Adrien A. Wilkie; Kristen Foley; Kristen M. Rappazzo; Thomas J. Luben (Science of The Total Environment, 2026)

Matched case-control study of air pollution and infant mortality in North Carolina - Thomas J. Luben; Alison K. Krajewski; Adrien A. Wilkie; Kristen Foley; Kristen M. Rappazzo (Environmental Research, 2026)

Advancing Earth System Science With the NASA Plankton, Aerosol, Cloud, Ocean Ecosystem ( PACE ) Satellite Mission - P. Jeremy Werdell; Brian Cairns; Skyelar A. Caplan; Ivona Cetinić; Sean R. Foley; Bryan A. Franz; Meng Gao; Zachary T. Fasnacht; K. Fred Huemmrich; Amir Ibrahim; Kirk D. Knobelspiesse; Antonio Mannino; et al. (Global Change Biology, 2026)
Earth observation satellites transform our understanding of Earth's biological, atmospheric, and surface systems. The Plankton, Aerosol, Cloud, ocean Ecosystem (PACE) mission, launched in 2024, represents NASA's latest investment in multidisciplinary Earth system science, building upon multi‐decadal heritage while introducing revolutionary capabilities. Since launch, PACE has extended and improved upon NASA's 30+ years of global satellite observations of our living ocean, atmosphere, and land, and initiated an advanced set of climate‐ and applications‐relevant data records. Mission goals include extending and improving upon systematic ocean color, aerosol, cloud, and terrestrial data records for Earth system studies, and addressing emerging science questions related to socioeconomic applications. PACE helps assess ocean health by determining the distribution of aquatic phytoplankton. In doing so, it is the first mission to provide daily, global measurements that will enable prediction of the “boom‐bust” cycle of fisheries, the appearance of harmful algae, and other factors that affect commercial and recreational industries. PACE also observes clouds and tiny airborne particles known as aerosols that influence air quality and absorb and reflect sunlight, thus warming and cooling the atmosphere. Many stakeholders rely on these key data to forecast weather, visibility, and air quality. Also, PACE provides novel and near‐daily views of land surfaces, collectively extending heritage vegetation time series while introducing novel terrestrial measurements previously only achievable at local scales. PACE ultimately provides observations that benefit Earth system research and society as a whole in ways that other current satellites cannot. As it passes its two‐year anniversary, the mission exemplifies how combining hyperspectral radiometry with multi‐angle polarimetry enables transformative Earth system science, addressing critical uncertainties while establishing new paradigms for integrated observations of our changing planet. This review examines how PACE fills critical gaps across aquatic, terrestrial, and atmospheric science disciplines.

Composition, Growth, Succession, and Function in the Cladophora Microbiome: Insights From Quantitative Stable Isotope Probing and NanoSIMS Imaging - Raina M. Fitzpatrick; Bruce A. Hungate; Mary Power; Megan Foley; Ty Samo; Egbert Schwartz; Micheala Hayer; Peter K. Weber; Jennifer Pett‐Ridge; Jane C. Marks (Environmental Microbiology, 2025)
The branching green macroalga Cladophora glomerata and its epiphytic microbiome dominate summer biomass in the Eel River, a Northern California river under Mediterranean (summer drought, winter rain) seasonality. Green Cladophora streamers proliferate in early summer, then change to yellow and then red‐brown as epiphyte loads increase. We characterised successional changes in epiphytic bacteria on Cladophora , examining both community composition and growth rates, using quantitative Stable Isotope Probing (qSIP) and 16S rRNA gene amplicon sequencing. The number of bacterial taxa increased with succession while growth rates peaked in the middle stage. NanoSIMS imaging confirmed high sulphur (S) concentrations in Cladophora cell walls relative to surrounding biomass, coinciding with a bloom of sulphur bacteria (bacteria that reduce or oxidise sulphur/sulphates). In general, relative abundances and growth rates were independent, indicating that either metric alone is insufficient for understanding how taxonomy and functional groups affect ecosystem processes. For instance, the relative abundance of nitrogen fixers peaked in the late summer when their relative growth rates were slowest. Such patterns may be driven by space competition limiting growth. Together, changes in abundance and relative growth rates suggest different limiting factors for different functional groups in the Cladophora microbiome at multiple successional stages.

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Middle Jurassic–Lower Cretaceous stratigraphy of the northern Great Australian Superbasin: insights from maximum depositional age constraints from the U–Pb detrital zircon record - E. K. Foley; E. M. Roberts; R. A. Henderson; C. N. Todd; E. M. Knutsen; C. Spandler (Australian Journal of Earth Sciences, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Dynamic Response of the Thoracolumbar and Sacral Spine to Simulated Underbody Blast Loading in Whole Body Post Mortem Human Subject Tests - Donald Sherman; Karthik Somasundaram; Paul Begeman; Sierra Foley; Jason Greb; Cynthia Bir; Constantine K. Demetropoulos; John M. Cavanaugh (Annals of Biomedical Engineering, 2021)

Trans-Tasman Cumulative Effects Management: A Comparative Study - Kathryn K. Davies; Karen T. Fisher; Gemma Couzens; Andrew Allison; Elizabeth Ingrid van Putten; Jeffrey M. Dambacher; Melissa Foley; Carolyn J. Lundquist (Frontiers in Marine Science, 2020)

A baseline analysis of coastal water quality of the port Honduras marine reserve, Belize: a critical habitat for sport fisheries - Brenna M. Sweetman; James R. Foley; Michael K. Steinberg (Environmental Biology of Fishes, 2019)

Sexual Health Concerns Among Cancer Survivors: Testing a Novel Information-Need Measure Among Breast and Prostate Cancer Patients - Sheila A. Crowley; Sallie M. Foley; Daniela Wittmann; Christina H. Jagielski; Rodney L. Dunn; Patricia M. Clark; Jennifer J. Griggs; Catherine Peterson; Marcia Leonard; Lawrence C. An; John T. Wei; James E. Montie; et al. (Journal of Cancer Education, 2016)

Seventy‐One Important Questions for the Conservation of Marine Biodiversity - E. C. M. PARSONS; BRETT FAVARO; A. ALONSO AGUIRRE; AMY L. BAUER; LOUISE K. BLIGHT; JOHN A. CIGLIANO; MELINDA A. COLEMAN; ISABELLE M. CÔTÉ; MEGAN DRAHEIM; STEPHEN FLETCHER; MELISSA M. FOLEY; REBECCA JEFFERSON; et al. (Conservation Biology, 2014)
The ocean provides food, economic activity, and cultural value for a large proportion of humanity. Our knowledge of marine ecosystems lags behind that of terrestrial ecosystems, limiting effective protection of marine resources. We describe the outcome of 2 workshops in 2011 and 2012 to establish a list of important questions, which, if answered, would substantially improve our ability to conserve and manage the world's marine resources. Participants included individuals from academia, government, and nongovernment organizations with broad experience across disciplines, marine ecosystems, and countries that vary in levels of development. Contributors from the fields of science, conservation, industry, and government submitted questions to our workshops, which we distilled into a list of priority research questions. Through this process, we identified 71 key questions. We grouped these into 8 subject categories, each pertaining to a broad component of marine conservation: fisheries, climate change, other anthropogenic threats, ecosystems, marine citizenship, policy, societal and cultural considerations, and scientific enterprise. Our questions address many issues that are specific to marine conservation, and will serve as a road map to funders and researchers to develop programs that can greatly benefit marine conservation. Setenta y Un Preguntas Importantes para la Conservación de la Biodiversidad Marina

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Effects of poaching on bull mating success in a free ranging African elephant (Loxodonta africana) population in Tarangire National Park, Tanzania - D. R. S. Ishengoma; A. M. Shedlock; C. A. H. Foley; L. J. Foley; S. K. Wasser; S. T. Balthazary; B. M. Mutayoba (Conservation Genetics, 2008)

Seasonal patterns in biomass smoke pollution and the mid 20th‐century transition from Aboriginal to European fire management in northern Australia - David M. J. S. Bowman; Joanne K. Dingle; Fay H. Johnston; David Parry; Michael Foley (Global Ecology and Biogeography, 2007)
Aim Globally, most landscape burning occurs in the tropical savanna biome, where fire is a characteristic of the annual dry season. In northern Australia there is uncertainty about how the frequency and timing of dry season fires have changed in the transition from Aboriginal to European fire management. Location In the tropical eucalypt savannas that surround the city of Darwin in the northwest of the Northern Territory of Australia. Methods Our study had three parts: (1) we developed a predictive statistical model of mean mass (µg) of particulates 10 µm or less per cubic metre of air (PM 10 ) using visibility and other meteorological data in Darwin during the dry seasons of 2000 and 2004; (2) we tested the model and its application to the broader air shed by (a) matching the prediction of this model to PM 10 measurements made in Darwin in 2005, (b) matching the predictions to independent measurements at two locations 20 km to the north and south of Darwin and (c) matching peaks in PM 10 to known major fire events in the region (2000–01 dry seasons); and (3) we used the model to explore changes in air quality over the last 50 years, a period that spans the transition from Aboriginal to European land management. Results We demonstrated that visibility data can be used reliably as a proxy for biomass burning across the largely uncleared tropical savannas inland of Darwin. Validations using independent measurements demonstrated that our predictive model was robust, and geographically and temporally representative of the regional airshed. We used the model to hindcast and found that seasonal air quality has changed since 1955, with a trend to increasing PM 10 concentrations in the early dry season. Main conclusions The results suggest that the transition from Aboriginal to European land management has been associated with an increase in fire activity in the early months of the dry season.

Seasonal patterns in biomass smoke pollution and the mid 20th-century transition from Aboriginal to European fire management in northern Australia - David M. J. S. Bowman; Joanne K. Dingle; Fay H. Johnston; David Parry; Michael Foley (Global Ecology and Biogeography, 2006)

MRI evaluation of topical heat and static stretching as therapeutic modalities for the treatment of eccentric exercise-induced muscle damage - R. C. Jayaraman; R. W. Reid; J. M. Foley; B. M. Prior; G. A. Dudley; K. W. Weingand; R. A. Meyer (European Journal of Applied Physiology, 2004)

Intraspecific variation in Eucalyptus secondary metabolites determines food intake by folivorous marsupials - I. R. Lawler; W. J. Foley; B. M. Eschler; D. M. Pass; K. Handasyde (Oecologia, 1998)

s of papers presented at the Fifty-Second Annual Meeting of The Potato Association of America - J. A. Crozier; P. J. Ito; Puente De La Fermin; S. J. Peloquin; P. Severino; E. C. Doll; D. R. Christenson; A. R. Wolcott; Hawkins Arthur; F. D. Howard; Herman Timm; W. J. Flocker; et al. (American Journal of Potato Research, 1968)